Pengaruh Modal, Tenaga Kerja, dan Lama Usaha Terhadap Pendapatan Pengrajin Industri Kerajinan Anyaman Di Desa Bona Kecamatan Blahbatuh Kabupaten Gianyar - Wulandari, Anak Agung Ratih; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 4, April 2017 (pp. 472 - 676), 2017)
In an effort to accelerate economic development, industrialization is One.The industrial sector is a mainstay for the economy sector in Indonesia. The industrial sector has contributed to the Gross Domestic Product (GDP) and employment opportunities for Timorese Indonesia . This research was done on the type of woven handicraft industry in the village of Bona Blahbatuh Gianyar regency. The study states that the capital is positive and significant influence simultaneously and partially on income, employment effect positive and significant effect simultaneously on the income, while the labor force is not positive and significant effect partially on income and long effort positive influence simultaneously and partially to income. This shows that increasing the amount of capital, the amount of labor and time effort then revenue will also increase.
Keywords: industri; modal; tenaga kerja; lama usaha; pendapatan